(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This study investigates how Project-Based Learning (PBL) contributes to improving English language instruction for preschool-aged children. Grounded in constructivist and sociocultural frameworks, the article analyzes the extent to which PBL promotes vocabulary growth, verbal communication skills, and social-emotional involvement. Based on a quasi-experimental design, data gathered from 4–5-year-old children in Uzbekistan reveal that PBL offers a natural and engaging environment for language development, encouraging learners through purposeful, experience-based activities.